Marfan syndrome: genetic variant determinants of cardiovascular outcomes. (14th October 2021) - Brogger, M N; Fernandez Ferro, G; Cardenas Reyes, I; Ochoa, J P; Garcia Hernandez, S; Fernandez, X; Garcia Giustiniani, D; Lamounier, A; Valverde, M; De La Higuera Romero, L; Ortiz Genga, M; Monserrat, L; et al.
Abstract: Background: Marfan syndrome is a systemic connective tissue disorder caused by genetic variants in the fibrillin-1 (FBN1) gene. Cardiovascular complications are the leading cause of mortality. Purpose: To compare cardiovascular outcome by gender and by type of the genetic variant in the FBN1 gene. Materials and methods: We analyzed clinical data on 1956 carriers and affected relatives with 1430 pathogenic or likely pathogenic genetic variants in the FBN1 gene (including cases identified in our laboratory and cases described in the literature) in whom age at last follow-up was available. We excluded patients with pathogenic or likely pathogenic genetic variants located in the so-called "neonatal region" (exon 24–32); they are recognized to have an early onset/severe phenotype. Kaplan-Meier survival curves were generated to examine gender and type of genetic variant in relation to survival free of surgical intervention or cardiovascular (CV) death (composite of deaths related to aortic dissection, heart failure/transplant, sudden, stroke or CV surgery). Genetic variants were classified as truncating (nonsense, frameshift and splicing), "missense non-neonatal" and only those missense eliminating a Cysteine residue in the non-neonatal region ("Cys non-neonatal"). Results: Data were examined on 896 patients with truncating variants (53% male; 47% female) and 1060 with missense variants, located outside the "neonatal region" (54% male; 46% female). Of these, 475 were missense variants substituting a cysteine residue (52% male; 48% female). Those with truncating variants had worse prognosis versus those with missense and Cys variants (p=0.000108 and p=0.000115), with earlier onset of cardiovascular events. Overall, patients with missense variants had similar prognosis to those with missense variants eliminating a Cysteine residue. By age 65, however, almost 50% of patients with any type of variant had suffered a CV event, and with each variant type males had worse prognosis (see Figure 1). This was most evident in males aged 30 to 50 with missense variants that substituted a Cysteine residue, while female carriers of these variants had a prognosis similar to other missense variants (see Figure 2). During the first decade carriers of missense and truncating variants mainly died of heart failure. From age 10 to 50, aortic dissection was the most common event, while later other events became more frequent, e.g. vascular intervention and sudden death. Conclusion: In our cohort, male carriers of pathogenic or likely pathogenic variants had worse prognosis versus females. Carriers of truncating variants had the worst CV outcomes. However, it is noteworthy that by age 65, regardless of gender or mutation type, close to 50% of patients had experienced a major CV event/death. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Health in Code